A MILITARY HISTORY OF MODERN SOUTH AFRICA - van der Waag, Ian (Scientia Militaria - South African Journal of Military Studies, 2015)
Surprisingly, in a country so involved in the twentieth-century’s major wars, with few exceptions, South African professional historians have for decades turned their backs on writing about the armed forces. It seemed that for the Afrikaner historians, the World Wars and the Union Defence Force were ‘English’ with only the Anglo-Boer War worthy of attention. The Anglophone historians, for their part, seemed to think that to show an interest in the armed forces would be to align themselves with Afrikaner nationalism and with apartheid. All too often, when professionals who ignore military studies become interested in writing their superficial knowledge is reflected in their approach to writing about military subjects.